Evaluation of uterine health by endometrial cytology and ultrasonography in the postpartum and its relationship with conception in alpacas - Deza Calsin, Hugo Wenceslao (2020)
The aim of this study was to evaluate the uterine health of alpacas by endometrial cytology (EC) using the cytobrush and uterine lavage techniques, to evaluate the uterine characteristics by ultrasound (US) and to relate them to the pregnancy rate. Multiparous (n=20) and primiparous (20) Suri alpacas of 29 ± 5 days postpartum were used. The percentage of polymorphonuclear (PMN) was determined in relation to the total number of cells present in the EC samples. The uterine ecotexture, presence of uterine content and the diameter of the uterine horns were determined by ultrasonography. Subsequent to the uterine evaluation, controlled breeding was performed, and pregnancy diagnosis was done 35 days later by US. A higher percentage of PMN (p<0.05) was observed in endometrial cytology samples obtained with the cytobrush technique compared to uterine lavage. The uterine horns had a heterogeneous ecotexture and no presence of content. The diameter of the left uterine horn was greater than that of the right uterine horn (p<0.05). There was no relationship between percentage of PMN and uterine horn diameter or pregnancy. Based on the results obtained, the EC would not allow an adequate assessment of uterine health, as there would be other factors involved in a greater chemotactic response of the PMN that promote their migration to the uterus. Ultrasonography allowed an objective assessment of uterine horns and uterine health and allowed early diagnosis of pregnancy.